Improving Children Health and Cognition: Evidence from School-Based Nutrition Intervention in India - Marion Krämer; Santosh Kumar; Sebastian Vollmer (Global Labor Organization (GLO), 2018)
We present experimental evidence on the impact of delivering double-fortified salt (DFS), salt fortified with iron and iodine, through the Indian school-feeding program called “mid-day meal” on anemia, cognition, and math and reading scores of primary school children. We conducted a field experiment that randomly provided a one-year supply of DFS at a subsidized price to public primary schools to prepare mid-day meal in one of the poorest regions of India. The DFS treatment had significantly positive impacts on hemoglobin levels and reduced the prevalence of anemia by 20 percent but these health gains did not translate into statistically significant impacts on cognition and test scores. While exploring the heterogeneity in effects, we find that treatment had statistically significant gains in anemia and test scores among children with higher treatment compliance. We further estimate that the intervention was very cost effective and can potentially be scaled up without much financial burden.
Keywords: C93; D04; I15; I18; I38; O11; 330; Double-fortified salt; education; anemia; cognition; school-children; mid-day meal; India; randomized controlled trial